ANALISIS STABILITAS LERENG DAN ALTERNATIF PENANGANANNYA : STUDI KASUS LONGSORAN PADA RUAS JALAN PRINGSURAT KM. MGL. 22+631 – 22+655 KABUPATEN TEMANGGUNG - Apri Luriyanto; Iqbal Maulana; Sri Prabandiyani Rento Wulandari; Indrastono Dwi Atmanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
This thesis contained about the stability of the soil and it countermeasures on roads Pringsurat KM. MGL. 22 +631 - 22 +655 District of Temanggung. Pringsurat landscape is hilly mountainous and prone to landslide. This road section is a class II national road built to connect cities in Central Java such as Semarang, Temanggung, Magelang with the cities of Yogyakarta. This road crosses the hills that contain layers of silt soil, clay, and sandy. Landslide occurred on roads Pringsurat KM. MGL. 22 +631 - 22 +655 District of Temanggung. The data used in this case study is primary data and secondary data. Data collection was conducted using interviews, direct observation in the field, and method literature. Method of analysis in this thesis is to calculate the slope stability and provide solutions to the problems that occur. Geotechnical analysis done in two ways, with the manual method and the program. Manual analysis method by Whitlow (1995) for multilayer soil while the program analyzes using Plaxis software V.8.2. Model of elastic and plastic collapse of Mohr-Coulomb criterion chosen as a model soil. The analysis showed that the landslide occurred at KM. MGL. 22 +631 - 22 +655. To deal with such matters tried with two alternatives, namely the handling of avalanches with geotextile type BW250 Woven and boored Pile, where the two alternatives are able to cope with the handling of landslides as evidenced by the results of the Safety Factor values 1.4114 and 1.4617 for Geotextile for boored Pile.